Bem-estar de estudantes de ensino fundamental: antecedentes e consequentes - Ferraro, Dandara Melynna Juliano (2023)
This dissertation will combine the studies in the Marketing area, particularly the Transformative Consumer Research (TCR) agenda, with the studies on educational services for children of 11 to 14 years of age from public and private schools. More specifically, it tries to understand which elements in the scholar environment influences the perceived well-being by these children and what are the consequences of this influence on their lives. To that end, exploratory qualitative research was conducted though the interview of 20 students from public and private schools. The content analysis of these interviews confirms the presence of 6 dimensions of subjective well-being of students: Personality; Culture/Values; Consumption; Social; Mentality; and Accomplishments, as well as their respective antecedents and consequences for the students.